The Ecological Validity of Picture SFON Tasks - Sophie Batchelor; Camilla Gilmore; Jayne Spiller; Matthew Inglis (Journal of Numerical Cognition)
Research has identified that children differ in the extent to which they spontaneously focus on numerical aspects of the environment (Spontaneous Focusing on Numerosity, SFON) and that this correlates with their mathematics achievement. It is assumed that the mechanism underpinning this relationship is that children who spontaneously focus on numerical features of their environment will experience more self-initiated practice with number concepts. We explored this mechanism by investigating whether 4- to 5-year-old children’s verbal SFON scores on a picture description task related to their spontaneous focusing on number while engaged in play activities with their parent. We found that the scores derived from a picture description task were strongly correlated with the scores derived from the play sessions, rₛ = .638, 95% CI [.433, .781], providing evidence for this mechanism. We further investigated the role that verbal abilities may play in children’s performance on the picture description task, finding that general verbal abilities were not associated with verbal SFON scores. These results contribute to our understanding of the role played by verbal SFON tendencies in explaining differences in numerical development, and demonstrate the ecological validity of SFON picture tasks.